2010
DOI: 10.1111/j.1467-9310.2010.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of competencies for professionals in open innovation teams

Abstract: In the open innovation management literature, it is widely acknowledged that individuals play a crucial role in collaborative knowledge creation processes. However, the literature tends not to explore the human side of open innovation teams. The present article therefore examines the competencies that professionals need for working in open innovation teams (specific but not necessarily unique to open innovation) and to cope with the challenges they face. A qualitative study consisting of explorative interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
0
22

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(189 citation statements)
references
References 31 publications
6
161
0
22
Order By: Relevance
“…being sociable, active, and talkative (Barrick and Mount, 1991), also coincide with the findings from the case studies in terms of interacting with others and functioning within teams. Being socially competent is also among the three most important competencies for individuals in OI teams according to a study by Du Chatenier et al (2010). Further relevant traits relating to OI that can be derived from the case studies are being brave and passionate.…”
Section: Discussionmentioning
confidence: 99%
“…being sociable, active, and talkative (Barrick and Mount, 1991), also coincide with the findings from the case studies in terms of interacting with others and functioning within teams. Being socially competent is also among the three most important competencies for individuals in OI teams according to a study by Du Chatenier et al (2010). Further relevant traits relating to OI that can be derived from the case studies are being brave and passionate.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies have been based on a work-oriented approach, grounded in rationalistic approach to competence suggesting a repertoire of fixed knowledge, skills, and abilities that constitute competent performance. For example, Chatenier et al (2010) identified 34 competencies, grouped into social and technical competences, that engineers need in order to act on challenges in open innovation teams. Hecker (1997) emphasized the importance of both technical and non-technical skills for engineers to successfully solve technical problems and simultaneously build a good relationship with colleagues and clients.…”
Section: Studying Mobile Project Workers' Liminality Competencementioning
confidence: 99%
“…Nevertheless, a great deal of research has addressed the topic of skills and competencies among engineers, often providing extensive lists of the various technical and social skills needed to perform engineering work successfully (e.g., Chatenier et al, 2010;Frank, 2006;Hecker, 1997;Nguyen, 1998). However, most of these studies have been based on a work-oriented approach, grounded in rationalistic approach to competence suggesting a repertoire of fixed knowledge, skills, and abilities that constitute competent performance.…”
Section: Studying Mobile Project Workers' Liminality Competencementioning
confidence: 99%
“…The work of du Chatenier et al (2010) on collaborative knowledge creation exemplified approaches that could trigger interesting research questions. The concept of knowledge exchange is now used by scholars interested in knowledge production for natural-resource management (Fazey et al, 2013;Cvitanovic et al, 2015b).…”
Section: Ideas For Further Researchmentioning
confidence: 99%